2020
DOI: 10.1186/s12889-020-08954-5
|View full text |Cite
|
Sign up to set email alerts
|

The ripple effect: a digital intervention to reduce suicide stigma among farming men

Abstract: Background: Compared with the general population, Australian farmers-particularly men-have been identified as at greater risk of suicide. A complex range of factors are thought to contribute to this risk, including the experience of Stigma. stigma also impacts those who have attempted suicide, their carers, and those bereaved by suicide-manifesting as shame, guilt, social isolation, concealment of death, reduced help seeking and ongoing risk of suicide. This paper evaluates the effectiveness of an intervention… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
1
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(45 citation statements)
references
References 43 publications
(54 reference statements)
1
40
1
3
Order By: Relevance
“…Not only was the peer-to-peer approach seen to be an authentic and acceptable, participants felt that a campaign where the message was delivered by another person, such as a family member or friend, would not be as powerful. Our findings contribute new insights and knowledge about the design elements required for developing effective lived experience suicide prevention videos, as shown in recent studies reporting on the effectiveness of videos targeting farmers [ 28 ] and lesbian, gay, bisexual, transgender, intersex, and queer communities [ 29 ]. These findings also suggest that a third-person approach, while well intentioned, may not engage the target audience of those contemplating suicide effectively.…”
Section: Discussionsupporting
confidence: 61%
“…Not only was the peer-to-peer approach seen to be an authentic and acceptable, participants felt that a campaign where the message was delivered by another person, such as a family member or friend, would not be as powerful. Our findings contribute new insights and knowledge about the design elements required for developing effective lived experience suicide prevention videos, as shown in recent studies reporting on the effectiveness of videos targeting farmers [ 28 ] and lesbian, gay, bisexual, transgender, intersex, and queer communities [ 29 ]. These findings also suggest that a third-person approach, while well intentioned, may not engage the target audience of those contemplating suicide effectively.…”
Section: Discussionsupporting
confidence: 61%
“…Hegemonic masculinity was reported as being mostly resisted. The hindering issues to men obtaining mental health treatment in the rural Australian context include stigma, lack of emotional expression, non-disclosure of distress, and barriers to seeking and getting help ( Kennedy et al, 2020 ). A retrospective study of bereaved men’s help-seeking before suicide found themes of complex relationships to seeking and getting help – there were those entrapped by secrecy and concealing the need for help, those with overwhelming illness that couldn’t be helped, as well as those whom services and systems provided ineffectual help ( Oliffe et al, 2020 ).…”
Section: Summary Of Men’s Mental Health and Suicidalitymentioning
confidence: 99%
“…Ripple Effect, an online intervention designed to reduce stigma among males in the Australian farming community with a lived experience of suicide, represents the greatest departure from the MHFA format in that it was designed solely to reduce suicide stigma among farmers [ 77 , 78 ]. Pre- and post-survey data failed to show any significant reduction in self- or perceived-stigma [ 78 ]. However, qualitative data and participant feedback suggested stigma reduction.…”
Section: Systematic Review Resultsmentioning
confidence: 99%